Kevalidan dan Kepraktisan Media E-Komik Sederhana Mitigasi Bencana Gempa untuk Siswa Kelas IV SD - Felicia Kezia Eudora; Nurul Istiq’faroh; Dea Rona Alfiyah; Rinta Putriana (Tumoutou Social Science Journal, 2026)
This study aims to develop a simple e-comic media for earthquake disaster mitigation to improve the reading skills of fourth-grade elementary school students. The method used is Research and Development (R&D) with the ADDIE model. The research subjects consisted of fourth-grade students and teachers at SDN Lidah Kulon IV. Data were collected through expert validation questionnaires, teacher practicality questionnaires, and student response questionnaires. The results showed that the e-comic media obtained a validity value of 91.67% with a very valid category. The practicality test by teachers obtained an average score of 3.5 (good), while the student response was 3.46 (very good). This shows that the e-comic media is easy to use, interesting, and effective in helping students understand disaster mitigation material while improving reading skills. Thus, the developed simple e-comic is suitable for use as an alternative Indonesian language learning media in elementary schools.